Learning to teach from the student's point of view: an ethical call from transformative learning. Issue 1 (2nd January 2021) - Simanjorang, Mangaratua; Taylor, Peter Charles; Ledger, Susan
ABSTRACT: Drawing on an autoethnographic inquiry we present a first-person, narrative account of a mathematics teacher's experience of developing an ethically responsible teaching practice. Reflective commentary on narrative vignettes illustrates the teacher's inquiry in the role of researcher as transformative learner. Inspired by transformative learning theory, he engaged in critical self-reflection on his moments of teaching, which prompted him to switch from the teacher's point of view and pay heed to his student's meaning perspective. This transformation of perspective enabled him to avoid conflict by negotiating a deal with the young resistant learner – 'a rebel kid' – to generate mutual respect, focus on values, and successfully adjust to the student's learning trajectory. The result of this inquiry suggests that endeavouring to teach from students' points of view is important not only for engaging meaningfully in an educative relationship but also for enhancing the sense of ethical responsibility of both teachers and students.